2017
DOI: 10.1016/j.neuropharm.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol: Effects on sexual behavior in male rats are mainly caused by its 5-HT reuptake blocking effects

Abstract: Tramadol is a well-known and effective analgesic. Recently it was shown that tramadol is also effective in human premature ejaculation. The inhibitory effect of tramadol on the ejaculation latency is probably due to its mechanism of action as a μ-opioid receptor agonist and noradrenaline/serotonin (5-HT) reuptake inhibitor. In order to test this speculation, we tested several doses of tramadol in a rat model of male sexual behavior and investigated two types of drugs interfering with the μ-opioid and the 5-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
4
15
2
Order By: Relevance
“…Our model is also fit to measure the effects of psychotropics in addition to antidepressants. We have studied various drugs, e.g., apomorphine, tramadol [62], and several serotonergic drugs and have found inhibitory, facilitatory, or no effects. The model is very useful to study the brain mechanisms underlying various aspects of sexual behavior and of sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Our model is also fit to measure the effects of psychotropics in addition to antidepressants. We have studied various drugs, e.g., apomorphine, tramadol [62], and several serotonergic drugs and have found inhibitory, facilitatory, or no effects. The model is very useful to study the brain mechanisms underlying various aspects of sexual behavior and of sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For the second experiment in slow ejaculating rats, animals were only administered S15535 in a randomized design similar to the first set of animals. As described previously in Olivier et al (2017), when pharmacological tests are performed, male rats are given a 30-min habituation time in the test boxes right after drug administration via IP injection, before the female rat is introduced. All behavior during the 30-min test is videorecorded after introduction of the female and were also livescored; the following parameters of the ejaculation series were deduced (Chan et al, 2011): number of ejaculations/test (E), number of mounts (M), number of intromissions (I), latency (s) to first mount (ML), latency (s) to first intromission (IL) and latency (s) to the first ejaculation (EL).…”
Section: Drug Treatment and Behavioral Experimentsmentioning
confidence: 99%
“…Because it is important to have comparable pharmacodynamics and kinetics in pharmacological studies, a test of fixed duration has been chosen: 30 min (1800 s). In the cases where drug-treatment had no "effect" on ejaculation and sexual behavior, or few or no animal achieved a first ejaculation it was not possible to perform statistical analyses and for those cases we assigned values of 1800 s (i.e., the maximum test duration) for some latencies (ejaculation, mount and intromission latency), although this is undoubtedly a matter of discussion as we have discussed before (Chan et al, 2011;Olivier et al, 2017). All tables and figures show the results for the first Ejaculation Series only.…”
Section: Drug Treatment and Behavioral Experimentsmentioning
confidence: 99%
“…Previously, we found ( Olivier et al, 2017a ) found that tramadol inhibits sexual behavior in male rats and postulated this to be mainly due to its SSRI properties, although tramadol’s μ-opioid receptor agonistic activity might contribute in a minor way to sexual behavior inhibition. Serotonergic activation of sexual activity in male rats is primarily based on activation of 5-HT 1A receptors based on the pro-sexual effects observed after 5-HT 1A receptor agonists ( Snoeren et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…In the present studies, based on our previous work ( Olivier et al, 2017a ), we first explored several doses of tramadol (5, 10, 20, 40, and 50 mg/kg IP) on sexual behavior of wild type (SERT +/+ ), heterozygous (SERT +/- ), or SERT -/- male rats, selected, and trained for average sexual activity (2–3 ejaculations per 30-min test after a 6-weeks training period). Because we knew from previous studies ( Olivier et al, 2017a ) that a higher tramadol dose (40 mg/kg) in wild type rats could only marginally be influenced by naloxone, we combined a slightly inhibitory dose of tramadol (20 mg/kg) in all three genotypes with naloxone, a μ-opiate receptor antagonist. In another set of studies, we combined tramadol (20 mg/kg) with a selected, sexual behavior-inactive dose of the 5-HT 1A receptor antagonist WAY100,635 (0.3 mg/kg).…”
Section: Introductionmentioning
confidence: 99%